2019
DOI: 10.1007/s00259-019-04343-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of the in vitro and in vivo stability of DFO, DFO* and DFOcyclo* for 89Zr-immunoPET

Abstract: Purpose Currently, the most commonly used chelator for labelling antibodies with 89 Zr for immunoPET is desferrioxamine B (DFO). However, preclinical studies have shown that the limited in vivo stability of the 89 Zr-DFO complex results in release of 89 Zr, which accumulates in mineral bone. Here we report a novel chelator DFOcyclo*, a preorganized extended DFO derivative that enables octacoordination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
89
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 35 publications
3
89
0
1
Order By: Relevance
“…However, new chelators are being developed and may improve the stability and biodistribution of 89 Zr-labeled mAbs such as [ 89 Zr]Zr-chDAB4, which can generate free [ 89 Zr]Zr IV and result in its uptake by bone. For example, Donnelly et al compared their novel chelator DFO-Sq to DFO-pPhe-NCS using the HER2-targeting antibody, trastuzumab[47] and Raave et al also indicated greater stability and less bone accumulation when DFOcyclo was used in preference to DFO to radiolabel trastuzumab with [ 89 Zr]Zr IV[48]. Consequently, the stability of the chelator together with the activity and antibody concentration[49] of [ 89 Zr]Zr-labeled mAbs will be important parameters to consider in planning future clinicals of [ 89 Zr]Zr-labeled chDAB4.…”
mentioning
confidence: 99%
“…However, new chelators are being developed and may improve the stability and biodistribution of 89 Zr-labeled mAbs such as [ 89 Zr]Zr-chDAB4, which can generate free [ 89 Zr]Zr IV and result in its uptake by bone. For example, Donnelly et al compared their novel chelator DFO-Sq to DFO-pPhe-NCS using the HER2-targeting antibody, trastuzumab[47] and Raave et al also indicated greater stability and less bone accumulation when DFOcyclo was used in preference to DFO to radiolabel trastuzumab with [ 89 Zr]Zr IV[48]. Consequently, the stability of the chelator together with the activity and antibody concentration[49] of [ 89 Zr]Zr-labeled mAbs will be important parameters to consider in planning future clinicals of [ 89 Zr]Zr-labeled chDAB4.…”
mentioning
confidence: 99%
“…It is consisted of three hydroxamate groups and forms a thermodynamically stable complex with zirconium. [35] The radioactivities distributing in the tumor showed significant heterogeneity by ex vivo immunohistochemistry and autoradiography. Abundant HER2 was expressed in the periphery of the tumor and the corresponding radio signal was strong.…”
Section: Discussionmentioning
confidence: 99%
“…Zr equilibrium with DFO is strongly shifted toward the complex, but remains rapidly reversible as demonstrated by the dissociating effect of excess free competing chelator, e.g., ethylenediaminetetraacetic acid. 55 Likewise, around 0.2% of 89 Zr was found to have dissociated during 24-hour incubation in plasma in vitro, 56 which would be subject to renal filtration with possibility of accumulating to PET-detectable levels in the small volume of kidneys. Given the patterns of 89 Zr tissue distribution dependence on the compound, be it chloride, oxalate or DFO chelate, 51 this is an aspect that needs to be considered whilst interpreting the tissue distribution data of 89 Zr-labeled proteins in immunoPET studies.…”
Section: Discussionmentioning
confidence: 99%